Oral Administration of Nonionic Water-Soluble Contrast Media to Treat Meconium Obstruction in Premature Infants: A Preliminary Study - Hong, Hyun Sook; Kim, Sung Shin; Park, Ga Young (Neonatal medicine (Seoul, Korea), 2021)
Purpose Meconium obstruction of prematurity (MOP) predisposes premature infants to intestinal perforation and prolonged hospitalization if not diagnosed and treated promptly. A standard contrast enema is less effective to treat infants with distal ileal obstructions because the contrast may not reach the obstructed areas. In an effort to avoid risky surgery, we administered oral contrast media to seven clinically diagnosed patients with MOP whose obstructions were not relieved via conventional sonography-guided contrast enema. We retrospectively evaluated whether oral nonionic water-soluble contrast media relieves MOP. Methods Seven of 67 premature infants with MOP were administered oral contrast media from June 2015 to January 2019. Patients were followed-up radiographically for bowel distention and evacuation of contrast media after oral administration. We recorded radiographic improvements, meconium evacuation, time to first feeding after oral contrast media administration, maternal history, and neonatal clinical factors. Results We evaluated five male and two female infants. The median gestational ages and body weights at birth were 27+5 weeks and 890 g, respectively. Radiography in five infants revealed multiple distended intestinal loops without air-fluid interfaces. Two infants had gasless abdomens, in which only stomach gas was visible. Oral contrast media (median, 2.5 mL) were administered at a median age of 7 days; five infants (5/7, 71.4%) responded to this treatment. The remaining two infants, who had ileal stenosis and hypoganglionosis, were surgically managed. Five infants (5/7, 71.4%) had maternal risk factors, and two (28.6%) were small for gestational age. Conclusion Nonionic oral water-soluble contrast medium can serve as a valuable adjunct treatment in premature infants with meconium obstruction.